The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.2528/pier10022404
|View full text |Cite
|
Sign up to set email alerts
|

Large Aperture Low Aberration Aspheric Dielectric Lens Antenna for W-Band Quasi-Optics

Abstract: Abstract-An advanced aspheric and asymmetric large aperture dielectric lens antenna is proposed firstly here for high resolution at Wband frequency. Large aperture and aspheric lens provides minimum focusing error and high resolution in millimeter wave quasi-optics application. To the best of the authors' knowledge we design first time 500 mm large aperture lens for W-band quasi optics application. Near field radiation pattern, beam size and focal length of the lens are obtained theoretically and experimentall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 9 publications
(9 reference statements)
0
17
0
Order By: Relevance
“…Many authors have demonstrated their design theories and experiment results of lens antenna for various applications [6] [7]. In this paper, the design of a W-band quasi optical lens antenna for short-range passive imaging is presented.…”
Section: Introductionmentioning
confidence: 99%
“…Many authors have demonstrated their design theories and experiment results of lens antenna for various applications [6] [7]. In this paper, the design of a W-band quasi optical lens antenna for short-range passive imaging is presented.…”
Section: Introductionmentioning
confidence: 99%
“…When compared with active imaging, MMW radiometric imaging does not radiate any form of radiation, and it offers the advantages of imaging covertly, eliminating specular effects and avoidance of interference with other systems [2]. Additionally, due to the superior capability of imaging through natural and manmade obscurants, MMW radiometric imaging has attracted increasing attention in broad areas ranging from precise guidance to concealed contraband detection [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, small bandwidth of high-order mode dielectric [9,10] and microstrip patch antennas [23,24] can constrainedly meet the lowest requirements of the 60-GHz WLAN. Although there are also wideband operations reported, they are limited by either the bulky dimensions [12,25,26] or omni-directional radiation patterns [27].…”
Section: Introductionmentioning
confidence: 99%